Hydrogen sorption characteristics of nanostructured Pd–10Rh processed by cryomilling. (1st January 2015) - Yang, Nancy; Yee, Joshua K.; Zhang, Zhihui; Kurmanaeva, Lilia; Cappillino, Patrick; Stavila, Vitalie; Lavernia, Enrique J.; San Marchi, Chris
Abstract: Palladium and its alloys are model systems for studying the solid-state storage of hydrogen. Mechanical milling is commonly used to process complex powder systems for solid-state hydrogen storage; however, milling can also be used to evolve nanostructured powder to modify hydrogen sorption characteristics. In the present study, cryomilling (mechanical attrition milling in a cryogenic liquid) is used to produce nanostructured palladium–rhodium alloy powder. Characterization of the cryomilled Pd–10Rh using electron microscopy, X-ray diffraction and surface area analysis reveal that (i) particle morphology evolves from spherical to flattened disk-like particles; while (ii) crystallite size decreases from several microns to less than 100 nm; and (iii) dislocation density increases with increased cryomilling time. Hydrogen absorption and desorption isotherms as well as the time scales for absorption were measured for cryomilled Pd–10Rh, and correlated with observed microstructural changes induced by the cryomilling process. In short, as the microstructure of the Pd–10Rh alloy is refined by cryomilling: (i) the maximum hydrogen concentration in the α-phase increases, (ii) the pressure plateau becomes flatter and (iii) the equilibrium hydrogen capacity increases at pressure of 101.3 kPa. Additionally, the rate of hydrogen absorption was reduced by an order of magnitude compared to non-cryomilled (atomized) powder.